Losy biblioteki benedyktynów z Krzeszowa - Franczyk-Cegła, Agnieszka (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
In 1919, the former Cistercian monastery in Krzeszów became home for German Benedictines who came from Czech Republic. Until World War II, they managed to amass an abundant library containing valuable collection of theological works.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne